Physical training, UCP1 expression, mitochondrial density, and coupling in adipose tissue from women with obesity - Cunha Brandao, Camila Fernanda; Carvalho, Flavia Giolo de; Souza, Anderson de Oliveira; Morandi Junqueira-Franco, Marcia Varella; Batitucci, Gabriela [UNESP]; Couto-Lima, Carlos Antonio; Fett, Carlos Alexandre; Papoti, Marcelo; Freitas, Ellen Cristini de [UNESP]; Alberici, Luciane Carla; Marchini, Julio Sergio (Wiley-Blackwell, 2019)
Background Exercise training may improve energy expenditure, thermogenesis, and oxidative capacities. Therefore, we hypothesized that physical training enhances white adipose tissue mitochondrial oxidative capacity from obese women. Objective To evaluate mitochondrial respiratory capacity, mitochondrial content, and UCP1 gene expression in white adipose tissue from women with obesity before and after the physical training program. Methods Women (n = 14, BMI 33 +/- 3 kg/m(2), 35 +/- 6 years, mean +/- SD) were submitted to strength and aerobic exercises (75%-90% maximum heart rate and multiple repetitions), 3 times/week during 8 weeks. All evaluated subjects were paired, before and after training for resting metabolic rate (RMR), substrate oxidation (lipid and carbohydrate) by indirect calorimeter, deuterium oxide body composition, and aerobic maximum velocity (V-max) test. At the beginning and at the ending of the protocol, abdominal subcutaneous adipose tissue was collected to measure the mitochondrial respiration by high-resolution respirometry, mitochondrial content by citrate synthase (CS) activity, and UCP1 gene expression by RT-qPCR. Results Combined physical training increased RMR, lipid oxidation, and V-max but did not change body weight/composition. In WAT, exercise increased CS activity, decreased mitochondrial uncoupled respiration and mRNA of UCP1. RMR was positively correlated with fat-free mass. Conclusion Physical training promotes an increase in mitochondrial content without changing tissue respiratory capacity, a reduction in mitochondrial uncoupling degree and UCP1 mRNA expression in WAT. Finally, it improved the resting metabolic rate, lipid oxidation and physical performance, independent of the body changing free, or fat mass in obese women.
Keywords: citrate synthase; human energy metabolism; mitochondria; obesity; physical training; uncoupling protein 1; white adipose tissue